PASSENGER SATISFACTION AND LOYALTY: A CASE OF INTER-CITY COACH TRAVEL IN MALAYSIA - Mokhlis, Safiek (Benefit: Jurnal Manajemen dan Bisnis, 2007)
The purpose of this paper is to investigate the relationship between service deliveryprocess, passenger satisfaction and loyalty in express coach industry in Malaysia. Fivecomponents of service process were identified: experience before tr avel, experience duringtravel, experience after travel, terminal facilities and bus operations. Data were solicited frompassengers of one express coach service plying a route of Kota Bharu to Kuala Lumpur using astructured questionnaire. Results show that three out of five areas of service process aresignificantly related with passenger satisfaction. Terminal facilities emerged as the best predictorfor passenger satisfaction, followed by the bus operations and experience after travel. Theanalysis also indicates a statistically significant correlation between passengersâ satisfaction andloyalty.